Optimización de un sistema de tratamiento de aguas residuales para la remoción eficiente de contaminantes en el mercado Caraguay - Flores Herrera, Daniel Alejandro (2024)
The thesis titled "Optimization of the Wastewater Treatment System for Efficient Contaminant Removal at Mercado Caraguay " focuses on improving thewastewater treatment process in one of the region's most active commercial areas. Mercado Caraguay, with its high commercial density, generates a large volume of wastewater containing elevated levels of contaminants. This study addresses the challenge of optimizing the existing wastewater treatment systemin the market to achieve more effective contaminant removal and comply with current environmental regulations. Initial analysis of the treatment system reveals that the current capacity is insufficient to efficiently handle the volume and contaminant load of the generated wastewater. Therefore, the main objective of the research is to design and implement improvements that enhance the efficiency of the treatment process.